2017
DOI: 10.18632/oncotarget.17123
|View full text |Cite
|
Sign up to set email alerts
|

Type Iγ phosphatidylinositol phosphate kinase regulates PD-L1 expression by activating NF-κB

Abstract: The programmed death-ligand 1 (PD-L1), by binding to PD-1 on the surface of immune cells, activates a major immune checkpoint pathway. Elevated expression of PD-L1 in tumor cells mediates tumor-induced T-cell exhaustion and immune suppression; therefore protect the survival of tumor cells. Although blockade of the PD-1/PD-L1 axis exhibits great potential in cancer treatment, mechanisms driving the up-regulation of PD-L1 in tumor cells remain not fully understood. Here we found that type Iγ phosphatidylinositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Similarly, targeted therapies for immune checkpoint blockade were found to be effective against tumors, whereas glial tumors in children require the SOX2 transcription factor, an embryonic neural stem cell antigen that is strongly implicated in the biology of glioma-initiating cells and acts as an antigenic molecule in anticancer immunity [ 21 , 22 ]. Although other transcription factors, including TP53 tumor suppressor and KRAS proto-oncogene in lung adenocarcinoma, are involved in PD-1 blockade immunotherapy [ 23 ], the correlation between lower NF-κB levels and GBM prognosis represents a potential therapeutic pathway by targeting the PD-L1/PD-1 axis and has also been reported in breast cancer [ 24 ]. In addition to the known transcription factor pathways, combined treatment via immune checkpoint blockade against PD-L1/PD-1 axis and suppression of NF-κB signaling targeting TNFRSF1B and/or LTBR could serve as an effective therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, targeted therapies for immune checkpoint blockade were found to be effective against tumors, whereas glial tumors in children require the SOX2 transcription factor, an embryonic neural stem cell antigen that is strongly implicated in the biology of glioma-initiating cells and acts as an antigenic molecule in anticancer immunity [ 21 , 22 ]. Although other transcription factors, including TP53 tumor suppressor and KRAS proto-oncogene in lung adenocarcinoma, are involved in PD-1 blockade immunotherapy [ 23 ], the correlation between lower NF-κB levels and GBM prognosis represents a potential therapeutic pathway by targeting the PD-L1/PD-1 axis and has also been reported in breast cancer [ 24 ]. In addition to the known transcription factor pathways, combined treatment via immune checkpoint blockade against PD-L1/PD-1 axis and suppression of NF-κB signaling targeting TNFRSF1B and/or LTBR could serve as an effective therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that inhibition of the NF-kB pathway leads to decreased PD-L1 expression in human NK/T cell lymphomas, melanoma cells, and primary monocytes (Bi et al, 2016;Gowrishankar et al, 2015;Huang et al, 2013). The observed binding of RELA (p65; a subunit of NF-kB) to the PD-L1 promoter in NSCLC cells (in the form of a RELA-MUC1-C complex), monocytes, and breast cancer cells suggests that NF-kB can directly regulate PD-L1 transcription (Bouillez et al, 2017;Huang et al, 2013;Xue et al, 2017). AP-1, a dimeric transcription factor consisting of c-Jun, FOS, MAF, or ATF subunits, is strongly oncogenic (Shaulian and Karin, 2002).…”
Section: B3gnt3mentioning
confidence: 99%
“…[ lymphoma (Marzec et al, 2008;Atsaves et al, 2017), melanoma (Jiang et al, 2013), HNSCC (Bu et al, 2017) RELA [ primary monocytes (Huang et al, 2013), melanoma (Gowrishankar et al, 2015), NSCLC (Bouillez et al, 2017), breast cancer (Xue et al, 2017) MUC1-C [ NSCLC (Bouillez et al, 2017) JUN [ lymphoma (Green et al, 2012), melanoma (Jiang et al, 2013) CDK5…”
Section: Stat3mentioning
confidence: 99%
“…Recent evidence has suggested that PD-L1, a key immune checkpoint molecule, has signal transduction capacities that contribute to tumor progression by regulating cell proliferation, migration, invasion and cancer stem cell expansion. 16 Since AKT3 was shown to function as an upstream activator of PD-L1 in breast cancer cells, 17 we tested whether the EMX2OS/miR-654/AKT3 axis promotes the aggressive phenotypes of OC cells in a PD-L1-dependent manner. Western blotting analysis demonstrated that PD-L1 was upregulated in OC cells compared with the normal ovary cell ISOE-80 ( Figure 7A).…”
Section: Emx2os Promotes Oc Cell Proliferation Invasion and Sphere Fmentioning
confidence: 99%